Central European hardwood trees in a high‐CO2 future: synthesis of an 8‐year forest canopy CO2 enrichment project. (28th August 2013) - Bader, Martin K.‐F.; Leuzinger, Sebastian; Keel, Sonja G.; Siegwolf, Rolf T.W.; Hagedorn, Frank; Schleppi, Patrick; Körner, Christian
Summary: Rapidly increasing atmospheric CO2 is not only changing the climate system but may also affect the biosphere directly through stimulation of plant growth and ecosystem carbon and nutrient cycling. Although forest ecosystems play a critical role in the global carbon cycle, experimental information on forest responses to rising CO2 is scarce, due to the sheer size of trees. Here, we present a synthesis of the only study world‐wide where a diverse set of mature broadleaved trees growing in a natural forest has been exposed to future atmospheric CO2 levels ( c . 550 ppm) by free‐air CO2 enrichment (FACE). We show that litter production, leaf traits and radial growth across the studied hardwood species remained unaffected by elevated CO2 over 8 years. CO2 enrichment reduced tree water consumption resulting in detectable soil moisture savings. Soil air CO2 and dissolved inorganic carbon both increased suggesting enhanced below‐ground activity. Carbon release to the rhizosphere and/or higher soil moisture primed nitrification and nitrate leaching under elevated CO2 ; however, the export of dissolved organic carbon remained unaltered. Synthesis . Our findings provide no evidence for carbon‐limitation in five central European hardwood trees at current ambient CO2 concentrations. The results of this long‐term study challenge the idea of a universal CO2 fertilization effect on forests, as commonly assumed in climate–carbon cycle models. Abstract : Synthesis. Our findings provide no evidence for carbon‐limitation in in the studied trees in a central European hardwood forest at current ambient CO2 concentrations. The results of this long‐term study challenge the idea of a universal CO2 fertilization effect on forests, as commonly assumed in climate‐carbon cycle models.